2006
DOI: 10.1021/ja057395c
|View full text |Cite
|
Sign up to set email alerts
|

Acid−Base Bifunctional and Dielectric Outer-Sphere Effects in Heterogeneous Catalysis:  A Comparative Investigation of Model Primary Amine Catalysts

Abstract: Dielectric and acid-base bifunctional effects are elucidated in heterogeneous aminocatalysis using a synthetic strategy based on bulk silica imprinting. Acid-base cooperativity between silanols and amines yields a bifunctional catalyst for the Henry reaction that forms alpha,beta-unsaturated product via quasi-equilibrated iminium intermediate. Solid-state UV/vis spectroscopy of catalyst materials treated with salicylaldehyde demonstrates zwitterionic iminium ion to be the thermodynamically preferred product in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(236 citation statements)
references
References 69 publications
5
229
2
Order By: Relevance
“…22 For instance, in the report by Bass et al, 22 amine-functionalized silica catalysts were prepared by bulk imprinting with protected amines. Before amine deprotection, the silanols were either capped with propyl groups (leading to a non-polar aprotic surface), capped with propylnitrile groups (leading to a polar aprotic surface), or left unmodified (with a surface both polar and protic).…”
Section: Cooperativity With the Silica Matrixmentioning
confidence: 99%
“…22 For instance, in the report by Bass et al, 22 amine-functionalized silica catalysts were prepared by bulk imprinting with protected amines. Before amine deprotection, the silanols were either capped with propyl groups (leading to a non-polar aprotic surface), capped with propylnitrile groups (leading to a polar aprotic surface), or left unmodified (with a surface both polar and protic).…”
Section: Cooperativity With the Silica Matrixmentioning
confidence: 99%
“…In fact, the 29 Si MAS NMR spectra of the bifunctional hybrids (Fig.5 curves b and c) exhibit bands from -50 ppm to -80 ppm assigned to T-type silicon (T 3 , T 2 and T 1 ) 65 species having a Si-C covalent bond, these signals being not present in the spectrum of siliceous material (curve a) synthesized for comparison, and then confirming that the hydrolysis and polycondensation of silylated-DMAN and MPTES occurs through reactive alkoxy terminal groups of the silylated moieties. In the 70 spectrum of DMAN-SO 3 H/SiO 2 -5-5 (curve b), it is possible to identify the T-bands corresponding to the T 1 (SiC(OH) 2 (OSi)), T 2 (SiC(OH)(OSi) 2 ) and T 3 (SiC(OSi) 3 ), whilst in the DMAN-SO 3 H/OMS-5-5 spectrum (curve c), only the band due to T 3 is visible, showing that more complete hydrolysis and poly-75 condensation of alkoxide terminal groups, present in the silane precursors, occur during the one-pot micellar route. In addition, three peaks at -92, -100 and -110 ppm are also present, due to Q 2 (Si(OH) 2 (OSi) 2 ), Q 3 (Si(OH)(OSi) 3 ) and Q 4 (Si(OSi) 4 ) silicon units respectively, 48 which are typical of highly siliceous 80 conventional mesoporous materials, associated to tetrahedrally coordinated silicon atoms conforming the solid network.…”
Section: Characterization Of Bifunctional Mesoporous Hybridsmentioning
confidence: 99%
“…Indeed, the weakly acidic silanol groups on the surface of silica have been previously recognized as capable of assisting various reactions. [23,[45][46][47][48][49] To test the participation of silanol groups in the catalytic process, we treated MAP-MSN-3.5 with hexamethyldisilazane (HMDS). 29 Si NMR showed that this reduced the number of silanols by 39% (from 3.8 to 2.3 mmol/g, Figure 4).…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 99%